2020
DOI: 10.21203/rs.3.rs-73170/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Rapid Blood Test to Monitor the Immune Status Change of Dairy Cows and to Evaluate their Disease Risk during the Periparturient Period

Abstract: BackgroundDairy cows are at the highest risk of developing clinical and subclinical diseases and disorders in the first few weeks following parturition. During the periparturient period, from approximately 30 days before calving to 30 days postpartum, the immune system of the dairy cows undergoes a multitude of changes to prepare for parturition, colostrum production and lactation. One such change is the transfer of a large amount of immunoglobulin G proteins, especially subclass IgG1 to colostrum, leading to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…To give a few examples, we found that the D2Dx immunity test score of mouse models and young calves is correlated directly to the humoral immunity development of the animals from neonates to adults ( 28 ). We found the D2Dx immunity test score changes dramatically in animals during pregnancy and parturition, and these changes reflect precisely the type of immunity changes that are expected during the reproduction process ( 29, 30 ). We also observed clearly the test score change in animals with virus infections compared to non-infected controls, and these test score changes mirror almost exactly the humoral immune responses in animals upon infection ( 28, 31 ).…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…To give a few examples, we found that the D2Dx immunity test score of mouse models and young calves is correlated directly to the humoral immunity development of the animals from neonates to adults ( 28 ). We found the D2Dx immunity test score changes dramatically in animals during pregnancy and parturition, and these changes reflect precisely the type of immunity changes that are expected during the reproduction process ( 29, 30 ). We also observed clearly the test score change in animals with virus infections compared to non-infected controls, and these test score changes mirror almost exactly the humoral immune responses in animals upon infection ( 28, 31 ).…”
Section: Introductionsupporting
confidence: 52%
“…We named this new test as D2Dx (from diameter to diagnostics) because the test is based on AuNP aggregate formation and we initially used particle size measurement for detection (28,(30)(31)(32). More recently, we have changed the detection method to a lower cost, and more convenient colorimetry method (29).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations